2012
DOI: 10.1111/j.1365-2621.2012.03163.x
|View full text |Cite
|
Sign up to set email alerts
|

Multitoxin evaluation in fermented beverages and cork stoppers by liquid chromatography–tandem mass spectrometry

Abstract: Summary A total of twenty‐eight mycotoxins were surveyed in wine (red, white and rose), cider (white and rose) and their cork stoppers from eight countries. Toxins of different fungi genera were detected as follows: Alternaria (ATs: alternariol – AOH; alternariol methyl – AME) and Penicillium/Aspergillus (ochratoxin A – OTA; penicillic acid – PAC). Toxins and levels varied with the sample types and country of origin. Wine presented contamination of OTA, AOH and AME. OTA was detected in forty‐one wine samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Various investigations conducted on dog food samples in South America and Turkey in the past decade have revealed a significant presence of aflatoxins in these products, with concentrations sometimes exceeding the maximum limits allowed by the respective national legislation (Sharma and Márquez, 2001;Maia and Pereira Bastos de Siqueira, 2002;Gunsen and Yaroglu, 2002;Scussel et al, 2006). In contrast, other studies recently conducted in several European countries showed only a modest presence of aflatoxinsin dog foods, often in non-quantifiable traces or, in any case, in very small concentrations (Martins et al, 2003;López Grío et al, 2010;Böhm et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations conducted on dog food samples in South America and Turkey in the past decade have revealed a significant presence of aflatoxins in these products, with concentrations sometimes exceeding the maximum limits allowed by the respective national legislation (Sharma and Márquez, 2001;Maia and Pereira Bastos de Siqueira, 2002;Gunsen and Yaroglu, 2002;Scussel et al, 2006). In contrast, other studies recently conducted in several European countries showed only a modest presence of aflatoxinsin dog foods, often in non-quantifiable traces or, in any case, in very small concentrations (Martins et al, 2003;López Grío et al, 2010;Böhm et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and rapid quantitative methods to measure Alternaria toxins would be very helpful for such studies. Recently, LC-MS/MS has been used to determine and confirm the presence of AOH and AME in apple juice and other fruit beverages at sub-nanogram per milliliter levels (Lau et al, 2003;Scussel et al, 2012). A multiphase method was developed by which 33 mycotoxins (including AOH and AME) in various products such as peanuts, pistachios, wheat, maize, cornflakes, raisins, and figs could be analyzed simultaneously (Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Scussel et al (2013) demonstrated the presence of various types of toxins in wines randomly collected from a retail market in the Netherlands. Ochratoxin A and penicillinic acid produced by Aspergillus spp.…”
Section: Alcoholic Beveragesmentioning
confidence: 99%